NEW UZBEKISTAN - A NEW MODEL OF FOREIGN POLICY (American Journal of Research in Humanities and Social Sciences, 2024)
From the first days of independence, Uzbekistan began to develop the conceptual and constitutional and legal foundations of its foreign policy, which laid the foundation for the establishment of foreign relations bodies of the Republic of Uzbekistan. The conceptual and legislative foundations of the foreign policy of the Republic of Uzbekistan are constantly being improved based on new challenges and threats.